Game of thrones among AUXIN RESPONSE FACTORs-over 30 years of MONOPTEROS research - Wójcikowska, Barbara; Belaidi, Samia; Robert, Hélène S (Journal of experimental botany, 2023)
For many years, research has been carried out with the aim of understanding the mechanism of auxin action, its biosynthesis, catabolism, perception, and transport. One central interest is the auxin-dependent gene expression regulation mechanism involving AUXIN RESPONSE FACTOR (ARF) transcription factors and their repressors, the AUXIN/INDOLE-3-ACETIC ACID (Aux/IAA) proteins. Numerous studies have been focused on MONOPTEROS (MP)/ARF5, an activator of auxin-dependent gene expression with a crucial impact on plant development. This review summarizes over 30 years of research on MP/ARF5. We indicate the available analytical tools to study MP/ARF5 and point out the known mechanism of MP/ARF5-dependent regulation of gene expression during various developmental processes, namely embryogenesis, leaf formation, vascularization, and shoot and root meristem formation. However, many questions remain about the auxin dose-dependent regulation of gene transcription by MP/ARF5 and its isoforms in plant cells, the composition of the MP/ARF5 protein complex, and, finally, all the genes under its direct control. In addition, information on post-translational modifications of MP/ARF5 protein is marginal, and knowledge about their consequences on MP/ARF5 function is limited. Moreover, the epigenetic factors and other regulators that act upstream of MP/ARF5 are poorly understood. Their identification will be a challenge in the coming years.
Keywords: DNA-Binding Proteins; Arabidopsis thaliana; meristem; Gene Expression Regulation, Plant; kyseliny indoloctové; Indoleacetic Acids; Arabidopsis Proteins; Transcription Factors; embryogenesis; proteiny huseníčku; auxin; transkripční faktory; flowering; plant; regulace genové exprese u rostlin; DNA vazebné proteiny; vascularization; transcription factor; Arabidopsis